Prevention of mother-to-child transmission (PMTCT) of HIV: a review of the achievements and challenges in Burkina-Faso - Ghoma Linguissi LS (Dove Medical Press, 2019)
Laure Stella Ghoma Linguissi1,2 Tani Sagna3,4, Serge Théophile Soubeiga1,4, Luc Christian Gwom,5 Céline Nguefeu Nkenfou6,5, Dorcas Obiri-Yeboah,7 Abdoul Karim Ouattara1,4, Virginio Pietra,4 Jacques Simpore1,41Laboratoire de Biologie Moléculaire et de Génétique, Université Ouaga I Pr Joseph Ki-Zerbo, Ouagadougou, Burkina Faso; 2Institut National de Recherche en Sciences de la Santé (IRSSA), Brazzaville, Republic of Congo; 3Institut de Recherche en Sciences de la Santé (IRSS), Ouagadougou, Burkina Faso; 4Centre de Recherche Biomoleculaire Pietro Annigoni (CERBA), Ouagadougou, Burkina Faso; 5“Chantal Biya” International Reference Centre for Research on HIV/Aids Prevention and Management (CBIRC), Yaoundé, Cameroon; 6Higher Teachers’ Training College, University of Yaoundé I, Yaoundé, Cameroon; 7Department of Microbiology and Immunology, School of Medical Sciences, University of Cape Coast, Cape Coast, GhanaBackground: Burkina-Faso’s HIV/AIDS program is one of the most successful in Africa, with a declining HIV prevalence and treatment outcomes that rival those of developed countries. Prevention of mother-to-child transmission (PMTCT) guidelines in Burkina-Faso, initiated in the year 2000, were revised in 2004, 2006 and 2010. The guideline document has since undergone several stages of improvement, largely based on recommendations from WHO, with adaptations by local experts in the field. Option B+ adopted since August 2014 in Burkina-Faso has enabled maintenance of mothers on longer treatment and increasing their survival and that of their children. Through this review, we describe the achievements and challenges of HIV PMTCT programs in Burkina-Faso.Aims of study: This study had the following objectives: 1) describing the historical perspective of PMTCT implementation in Burkina-Faso; 2) presenting the effectiveness of interventions at improving PMTCT service delivery and promoting retention of mothers and babies in care; and 3) determining the impact of male partner involvement on PMTCT in Burkina-Faso.Methodology: A literature search was conducted in PubMed and Google. Search terms included the following keywords: “HIV testing”; “prevention”; “mother”; “child”; “male partner”; “counseling”; “involvement”; “participation”; and the grouped terms “PMTCT and partners”; “VCT”; “barriers and/or factors”; “Male involvement in PMTCT”; and “Burkina-Faso”. Data collection took place from May to October 2015. The search was limited to articles published between January 2002 and December 2015. UNICEF and UNAIDS web sites were also used to find relevant abstracts and documents.Results: Studies have revealed that with PMTCT, HIV transmission rate moved from 10.4% in 2006 to 0% in 2015. The PMTCT program remains the best way to care for HIV-infected pregnant women and their babies. The current PMTCT policy is based on evidence that male partner involvement is associated with women’s completion of PMTCT.Conclusion: This study shows that the reduction in mother to child transmission of HIV in Burkina-Faso over the years is mainly due to the improvement of PMTCT programs. Efforts still need to be made about the involvement of male partners.Keywords: HIV/AIDS, PTMTCT, HAART, Burkina Faso